2008
DOI: 10.1111/j.1525-1594.2007.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hemolytic Properties of Different Shapes of Occlusion of Blood Sac in Occlusive‐type Pulsatile Blood Pump

Abstract: The occlusive-type pulsatile extracorporeal blood pump (T-PLS, Seoul National University, Seoul, Korea) received the Communauté Européenne mark of the European Directives (2003) and Korea Food and Drug Administration approval (2004) for short-term application as an extracorporeal life support system. The pump system was recently upgraded in the ameliorated actuator head for reducing hemolysis, rather than in the existing actuator head. In this study, the hemolytic performance of the new pump system (assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A simulation was performed using the commercial package, LS‐DYNA (Livermore Software Technology Cooperation, Livermore, CA, USA) (4). In the previous article, the hemolysis results of two different pusher plates (fixed type, roller type) were compared (1). However, in this study, only one pusher plate, the roller type that showed better hemolysis results in a previous study, was used and blood flow analysis was not considered as hemolysis or flow pattern.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…A simulation was performed using the commercial package, LS‐DYNA (Livermore Software Technology Cooperation, Livermore, CA, USA) (4). In the previous article, the hemolysis results of two different pusher plates (fixed type, roller type) were compared (1). However, in this study, only one pusher plate, the roller type that showed better hemolysis results in a previous study, was used and blood flow analysis was not considered as hemolysis or flow pattern.…”
Section: Methodsmentioning
confidence: 98%
“…In a previous study, we presented an important parameter that affects hemolysis with occlusive pumps—the shape of the occlusion (folding pattern) of the blood sac (1). The Twin‐Pulse Life Support System (T‐PLS; Seoul National University and Korea University, Seoul, Korea) is a pulsatile extracorporeal life support system that was developed in Korea (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hyuk Choi et al. (4) of the Seoul National University, Seoul, Korea compared the hemolytic properties of different shapes of occlusion of the blood sac in an occlusive‐type pulsatile blood pump. The hemolytic performance was affected by the degree of the occlusiveness and was lower than the control roller pump.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%